Ownership effect of fractional reserve banking:an islamic perspective - Larbani, Moussa; Mydin Meera, Ahamed Kameel (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to show that fractional reserve banking (FRB) has implications for the ownership structure of assets in the economy that violates the Islamic principles of ownership.